Presence of Zea luxurians (Durieu and Ascherson) Bird in Southern Brazil: Implications for the Conservation of Wild Relatives of Maize - Silva, Natália Carolina de Almeida; Vidal, Rafael; Costa, Flaviane Malaquias; Vaio, Magdalena; Ogliari, Juliana Bernardi (PLOS ONE, 2015)
Records of the occurrence of wild relatives of maize in South American lowlands are unprecedented, especially in sympatric coexistence with landraces. This fact is relevant, because regions of occurrence of wild relatives of cultivated plants should be a priority for conservation, even if they do not correspond to the center of origin of the species. The aim of this study was to identify and characterize the wild relatives of maize in the Far West of Santa Catarina, southern Brazil. Therefore, phenotypic characterization was performed for five populations, based on 22 morphological traits deemed as fundamental for classifying the species of the genus Zea, and validated through the characterization of chromosomal knobs of two populations. The occurrence and distribution of teosinte populations were described through semi-structured interviews applied to a sample of 305 farmers. A total of 136 teosinte populations were identified; 75% of them occur spontaneously, 17% are cultivated populations, and 8% occur both ways, for the same farm. Populations that were characterized morphologically had trapezoidal fruits mostly, upright tassel branch (4–18), non-prominent main branch and glabrous glumes, with two protruding outer ribs and 8 inner ribs, on average. Cytogenetic analysis identified 10 pairs of homologous chromosomes (2n = 20) with 26 knobs, located in the terminal region of all chromosomes. The similarity of these results with the information reported in the literature indicates that the five populations of wild relatives of maize in this region of Santa Catarina belong to the botanical species Zea luxurians.